The concept of tasamuh : a study of Najm al-Din al-Tufi's thought - Rokhman, Mauhibur (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This study focuses on Najm al-Din al-Tufi's thought which relates to the concept of tasamuh formulated and practiced by him. It begins with a discussion on the background of al-Tufi's life to understand who al-Tufi is and analyse his life experience. He is a brilliant prolific Muslim scholar who can be identified as an independent scholar in terms of his unwillingness follow mainstream. In addition, it is continued with an exploration on how the idea of tasamuh develops in Islam and the Western. By explaining the development of tasamuh it is understood that tasamuh practiced by him which is based on al-Qur'an and hadith as well as ijtihad is not line with what people refer to as tolerance in today's context. Al-Tufi's tasamuh was not only practiced by him towards Muslim people, but also towards non-Muslims. It is very interesting that al-Tufi himself implemented tasamuh in his daily activies considering that he lived in chaotic circumstances and was a victim of mihnah. It is obvious that al-Tufi's concept of tasamuh should be deemed as either an alternative or a solution for all Muslims to involve in social interaction without removing the identity of being Muslim.